Dimensionamento estocástico de geração de energia solar fotovoltaica aplicado a consumidores em média tensão - estudo de caso - Duarte, Rosangelo Jeronimo da Costa (2023)
Recently, a significant change was implemented in Brazilian legislation regarding the compensation of surplus energy generated by photovoltaic systems (SFV). This change aims to transform the way in which billing for the use of the electricity distribution network is carried out. Now, billing is based on the injection of demand measured in kilowatts (kW), using the concessionaire's Distribution System Use Tariff, known as TUSDg. Previously, projects were charged by the Distribution System Use Tariff – Load (TUSDc), which meant that they paid for the injected electrical power (surplus) or for the cost of system availability. With the recent change, there was a separation in tariff costs, distinguishing load demand (kW) from generation demand (injection in kW). This separation consolidated the calculation of the Tariff for use of the Distribution System (TUSDg) into the portion referring to the active energy injected into the network, thus impacting the way in which load demand is contracted and how local generation demand is supplied to Group A consumers. With this in mind, this study aims to carry out a case study in the sizing of an SFV for the commercial building of the Federal University of Latin American Integration (UNILA), called Campus Integração in Foz do Iguaçu-PR, in order to verify the impact of this change. Using stochastic sizing, the aim is to determine a system capable of injecting a specific amount of demand into the electricity grid, while also considering the probability of injecting generation demand in different scenarios. In the analysis, both deterministic and stochastic sizing are taken into account, the local selfconsumption generation of the SFV, comparing the results and determining the financial return of the project in different scenarios and in accordance with the compensation rules established in Law 14.300/2022.